The Sketch - Long, Nathan; Hush, Shannon; Hergott, Ryan; Nguyen, Vy (My University, 2016)
Credits: Story-Nathan Long, Shannon Hush, Ryan Hergott. Director-Nathan Long. Cinematography-Nathan Long, Vy Nguyen. Post Production-Shannon Hush, Nathan Long, Ryan Hergott, Vy Nguyen. Cast- Ryan Hergott, Nathan Howe. Extras-Justin Cain, Cooper Dahms, Alex Kuchinskas, Lindsey Leardi, Brent Higgins, Kelly Pyle, Nathan Long, Shannnon Hush, Vy Nguyen.
Citation: Story Arc. (2016). The Sketch. K-State 48 Film Festival, 2016
Keywords: Story Arc; K-State 48 Film Festival